2017
DOI: 10.1172/jci91913
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations and progressive monosomy modify SAMD9-related phenotypes in humans

Abstract: It is well established that somatic genomic changes can influence phenotypes in cancer, but the role of adaptive changes in developmental disorders is less well understood. Here we have used next-generation sequencing approaches to identify de novo heterozygous mutations in sterile α motif domain–containing protein 9 (SAMD9, located on chromosome 7q21.2) in 8 children with a multisystem disorder termed MIRAGE syndrome that is characterized by intrauterine growth restriction (IUGR) with gonadal, adrenal, and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
217
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(237 citation statements)
references
References 32 publications
11
217
0
9
Order By: Relevance
“…In the report by Buonocore et al , two out of four patients with two mutations died very early, and the remaining two patients developed myelodysplastic syndrome with monosomy 7 3. Probably due to these reasons, the proportion of the revertant cells did not reach to 100% 3. Hence, the two patients described in this study are the first patients who achieved complete haematological reversion.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In the report by Buonocore et al , two out of four patients with two mutations died very early, and the remaining two patients developed myelodysplastic syndrome with monosomy 7 3. Probably due to these reasons, the proportion of the revertant cells did not reach to 100% 3. Hence, the two patients described in this study are the first patients who achieved complete haematological reversion.…”
Section: Discussionmentioning
confidence: 55%
“…For patient 2, although we could not test whether p.Gln39* was a somatic mutation since the patient has already died, skewed X chromosome inactivation in leucocytes was shown, indicating their monoclonality. Simultaneous detection of one activating and another inactivating SAMD9 mutation in MIRAGE syndrome have already been reported by Buonocore et al ,3 although colocalisation of two mutations on the same allele was not confirmed. In the report by Buonocore et al , two out of four patients with two mutations died very early, and the remaining two patients developed myelodysplastic syndrome with monosomy 7 3.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Schwartz et al [42] identified these mutations in 17% of pediatric MDS patients. Germline variants in SAMD9 and SAMD9L have been associated with multisystem disorders with a range of systemic abnormalities, including cytopenia, infection, intrauterine restriction of growth, adrenal hypoplasia, abnormal genital phenotypes, progressive cerebellar dysfunction, and enteropathy [43][44][45][46]. To date, there are no reports of expected BM morphology in mutation carriers.…”
Section: Other Recently Described Myeloid Neoplasms With Germline Prementioning
confidence: 99%
“…The genes implicated are diverse, including well-known hematopoietic transcription factors such as CEBPA, GATA2, and RUNX1 as well as genes such as BRCA1 and MSH6 , more traditionally thought of as solid tumor risk genes [10]. The most recently identified genes, DDX41, SAMD9 and SAMD9L , are revealing novel pathways involved in leukemogenesis and deepening our understanding of the basic biology of MDS/AML [1113]. In recognition of the impact of this growing field on clinical care, the World Health Organization, European Leukemia Net, and National Comprehensive Cancer Network have all recently incorporated consideration of MDS/AML germ line predisposition syndromes into MDS/AML classification and clinical management guidelines, making knowledge of these syndromes now essential for clinicians and pathologists alike [1416].…”
Section: Inherited Genetics In Myelodysplastic Syndrome and Acute Myementioning
confidence: 99%